Charting the Future of the Ginans: Needs and Expectations of the Ismaili Youth in the Western Diaspora - Tharani, Karim (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2022)
Objective – The heritage of ginans of the Nizari Ismaili community comprises hymn-like poems in various Indic dialects that were transmitted orally. Despite originating in the Indian subcontinent, the ginans continue to be cherished by the community in the Western diaspora. As part of a study at the University of Saskatchewan, an online survey of the Ismaili community was conducted in 2020 to gather sentiments toward the ginans in the Western diaspora. This article presents the results of the survey to explore the future of the ginans from the perspective of the English-speaking Ismaili community members.Methods – An online survey was developed to solicit the needs of the global Ismaili community using convenience sampling. The survey attracted 515 participants from over 20 countries around the world. The English-speaking members of the Ismaili community between 18 to 44 years of age living in Western countries were designated as the target group for this study. The survey responses of the target group (n = 71) were then benchmarked against all other respondents categorized as the general group (n = 444).Results – Overall, 85% of the respondents of the survey were from the diaspora and 15% were from the countries of South Asia including India, Pakistan, and Bangladesh. The survey found that 97% of the target group respondents preferred English materials for learning and understanding the ginans compared to 91% in the general group. Having access to online ginan materials was expressed as a dire need by respondents in the two groups. The survey also revealed that over 90% of the respondents preferred to access private and external ginan websites rather than the official community institutional websites. In addition, the survey validated the unified expectations of the community to see ginans become an educational and scholarly priority of its institutions.Conclusion – Based on the survey results, it can be concluded that the respondents in the target group are educated citizens of English-speaking countries and regard the heritage of ginans to be an important part of their lives. They value the emotive and performative aspects of the tradition that help them express their devotion and solidarity to the Ismaili faith and community. They remain highly concerned about the future of the ginans and fear that the teachings of the ginans may be lost due to lack of attention and action by the community institutions. The development and dissemination of curriculum-based educational programs and resources for the ginans emerged as the most urgent and unmet expectation among the survey respondents. The article also identifies actions that the community institutions can take to ensure continued transmission and preservation of the ginans in the Western diaspora.